1980
DOI: 10.1159/000131509
|View full text |Cite
|
Sign up to set email alerts
|

Location of the 18S and 28S rRNA cistrons in the genome of the domestic rabbit (<i>Oryctolagus cuniculus</i> L.)

Abstract: The genomic location of rDNA in the rabbit was determined by in situ hybridization with 125I-labeled ribosomal RNA (rRNA). The results demonstrate the presence of rRNA genes on chromosomes 13, 16, and 20, all of which have secondary constrictions, and on the telomere of the long arm of 21. The number of genes, as assessed by grain counts, was not equally distributed among the chromosomes. Chromosome 20 had the most copies and along with 13 and 16 carried significantly more genes than 21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Our data are in agreement with previous studies in the rabbit in which nucleolar organizer regions were identified at the same locations by sequential Qbanding and silver staining (Martin-DeLeon et al, 1978). Furthermore, the present data confirm the localization that was achieved by hybridization of RNA probes in radioactive in situ hybridization experiments (Martin-DeLeon, 1980). Hybridization with DNA isolated from BAC clones resulted, in general, in clear fluorescent spots.…”
Section: Resultssupporting
confidence: 93%
“…Our data are in agreement with previous studies in the rabbit in which nucleolar organizer regions were identified at the same locations by sequential Qbanding and silver staining (Martin-DeLeon et al, 1978). Furthermore, the present data confirm the localization that was achieved by hybridization of RNA probes in radioactive in situ hybridization experiments (Martin-DeLeon, 1980). Hybridization with DNA isolated from BAC clones resulted, in general, in clear fluorescent spots.…”
Section: Resultssupporting
confidence: 93%
“…In a great number of mammalian species, the location of the genes coding for 18s and 28s ribosomal RNA (rRNA genes or rDNA) has been determined by in situ hybridization (Evans et al 1974;Henderson et al 1974;Hsu et al 1975;Martin-DeLeon 1980). In the domestic pig, application of this method has revealed that the rRNA genes are located either in the secondary constriction of chromosome no.…”
Section: Introductionmentioning
confidence: 99%
“…The only possible comparison of Ag-NOR position is with Oryctolagus cuniculus (Martin-DeLeon 1980 ;Martin-DeLeon et al 1978 ;Monteagudo and Arruga 1991); this species shows the occurence of Ag-NORs in three pairs of chromosomes which might correspond to those of L. starcki, but also in a pair of small acrocentrics which do not find any homologue in our data.…”
Section: Resultsmentioning
confidence: 51%